Analisis Kepadatan Tanah Pada Akses Jalan Conveyor PLTU TJB Unit 3,4 Dengan Menggunakan Standar AASHTO T 191 - Fahrizal, Yusuf; Adi Saputro, Yayan; Rochmanto, Decky (Jurnal Civil Engineering Study, 2022)
In connection with the mobilization of large vehicles in the PLTU TJB unit 3,4 conveyor area, a road is needed, to build roads it is necessary to pay attention to compaction of the subgrade so that there is no damage such as land subsidence and other construction failures caused by compaction that is not up to standard. The method used is an experimental method, the data used are secondary data obtained from the site pland road with a length of 747 m, the number of sandcone test points is 32 points, the primary data is directly taken from the research object, laboratory testing includes soil properties, compaction, and soil density testing. with the standard sandcone method AASHTO T 191, the results of the soil property test containing gravel, coarse sand, medium sand, fine sand, the type of grain all contain fly ash and bottom ash material, the compaction test obtained Lab max 1.610 gr/cm3, with water content optimum 11,111%, there are several STAs that have not met Field moisture content for compaction is (-1% + 3%) against OMC, the AASHTO T 191 standard sandcone test obtained an average (R) 95,861%, previously correction was made to the aggregate retained in sieve no.4.